Analysis of Gender-Based Computational Thinking Skills through Project Base Learning (PjBL) Programming Learning Using Fuzzy Method - Fitri*, Zahratul; Safriana, Safriana; Meiyanti, Rini; Faisal, Muhammad; Mamat, Rizalman Bin (Jurnal Pendidikan Sains Indonesia, 2024)
Learning Evaluation is carried out to determine the level of competence possessed by students. Computational Thinking is a learning approach used to improve students' cognitive thinking. Gender-based education is important to be implemented in all educational institutions because men and women have equal rights in obtaining education. Female students are often considered to have more weaknesses in learning technical practices than men, so it is expected to advance the thinking of students, especially gender equality between men and women in thinking in order to be able to compete in the world of work. This study aims to train how to think in solving problems using several techniques in Project Base Learning (PjBL)-based programming learning whose learning evaluation results between male and female students are analyzed using Tsukamoto's Fuzzy Inference method. The results obtained were the development of computational thinking of students totaling 40 people including 20 men and 20 women obtained 4 male students and 3 female students with "very high" scores, 5 male students and 5 female students obtained "High" scores, 8 male students and 12 female students obtained "Medium" scores, 2 male students obtained "Low" grades, while 1 male student obtained a score of "Very Low". This proves that the implementation of the concept of computational thinking in project-based learning (PjBL) programming learning can increase the level of thinking skills of students in doing learning.